Time interval from initial surgery for torn discoid lateral meniscus to the contralateral knee surgery - Takahisa Sasho; Hiroaki Tsuruoka; Masahiko Saito; Ryuichiro Akagi; Yuta Muramatsu; Shunsuke Mukoyama; Satoshi Yamaguchi (Elsevier, 2014)
To estimate the long-term possibility of needing surgery on contralateral knees that were asymptomatic at the time of initial discoid lateral menisci (DLM) surgeries, a minimum of 10 years of follow-up was performed after unilateral surgery for a torn DLM. Eligible patients had received arthroscopic meniscectomy between 1986 and 2001 for unilateral torn DLM. Patients with symptomatic contralateral knees at the time of initial surgery were excluded. Among these patients, only those aged no more than 20 years at the time of surgery were included in the study. Ultimately, 30 contralateral knees were followed for an average of 16.6 years after the initial knee surgery. Types of menisci were examined from operative records employing Watanabe's classification. When surgical treatment was necessary on contralateral knee, time interval from initial surgery to the second surgery was recorded. Patients were divided into two groups: those who needed surgical treatment on their contralateral knees (surgery group: S group) and those who did not need surgical treatment on their contralateral knees (non-surgery group: N group). Age at the time of initial surgery, sex, and type of menisci were examined and compared between the two groups. Seven of the 30 knees received arthroscopic surgery during the follow-up period (at an average of 1.6 years after the initial surgery). The rest of the 77% of contralateral knees survived a follow-up period of at least 10 years without requiring surgery. A higher percentage of female patients needed contralateral knee surgeries (30%, 6/20 patients) compared with male patients (10%, 1/10 patients). The possibility for needing surgery on the contralateral knee was highest in the first 2 years and decreased drastically thereafter.